Prognostic significance of increased urinary neopterin concentrations in patients with breast carcinoma - Kalábová, H; Krcmová, L; Kasparová, M; Plísek, J; Laco, J; Hyspler, R; Klozová, H; Solichová, D; Melichar, B (European journal of gynaecological oncology, 2011)
Increased serum or urinary concentrations of neopterin have been described in patients with tumors of different primary locations, but reports on neopterin in patients with breast carcinoma are relatively innumerous. We have evaluated urinary neopterin in 456 patients with breast carcinoma. Urinary neopterin was determined using high-performance liquid chromatography. Neopterin in patients was increased only in a minority of patients with breast carcinoma. Increased urinary neopterin was associated with inferior overall survival. Prognostic significance of increased urinary neopterin was evident in patients with tumors expressing hormone receptors or/and human epidermal growth factor receptor (HER)-2, but not in patients with triple negative tumors. Among other parameters determined, C-reactive protein, hemoglobin, peripheral blood neutrophil count and platelet count were significant prognostic factors. On multivariate analysis, age, expression of hormone receptors, neutrophils, stage and hemoglobin concentration were independent prognostic indicators. In conclusion, serum neopterin is increased only in a minority of patients with breast carcinoma. Increased urinary neopterin was predictive of poor survival in univariate, but not multivariate analysis. Age, expression of hormone receptors, neutrophils, stage and hemoglobin concentration were independent prognostic indicators.
Keywords: Chromatography, High Pressure Liquid; nádory prsu; C-Reactive Protein; Platelet Count; Leukocyte Count; erbB receptory; Neutrophils; ErbB Receptors; Humans; neutrofily; hemoglobiny; receptory pro estrogeny; prognóza; Receptors, Progesterone; Prognosis; Female; Neopterin; Hemoglobins; počet leukocytů; ženské pohlaví; počet trombocytů; receptory progesteronu; neopterin; Receptors, Estrogen; multivariační analýza; C-reaktivní protein; lidé; vysokoúčinná kapalinová chromatografie; Multivariate Analysis; Breast Neoplasms